Double encapsulation of liquid active compounds using nanoclay reinforced polyurea microcapsules - Aher, Yogeshwar P.; Torris, Arun; Adhikari, Benu; Shukla, Ravi; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2023)
In recent years, there has been growing interest in the double encapsulation of drugs, agrochemicals, and fragrances, aiming to achieve the highest encapsulation efficiency and preserve the activity of the encapsulated core over an extended duration. However, when active ingredients in liquid form are double encapsulated, preventing the rupture of primary microcapsules during the second encapsulation process and the leakage of the encapsulated core are major challenges. This report describes a method that utilizes polyurea and starch for successful double encapsulation of dimethyl phthalate (DMP), a liquid insect-repellent, as a model active component. We demonstrate that the incorporation of 3 wt% montmorillonite (MMT) nanoclay strengthens the polyurea wall of the primary microcapsule and prevents its rupture during double encapsulation with starch. This process facilitates the uniform distribution of polyurea microcapsules within the starch matrix and significantly improves the mechanical integrity of the nanocomposite microcapsules embedded in starch. The double-encapsulated system developed in this study significantly reduces the release rate of encapsulated DMP.
Keywords: Controlled release; Double encapsulation; Microcapsules; Microencapsulation; Nanocomposites; Starch matrix